2015
DOI: 10.4172/jpb.1000361
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Human Proteome in Subcutaneous and Visceral Fat Depots in Diabetic and Non-diabetic Patients with Morbid Obesity

Abstract: No longer regarded as simply a storage depot, fat is a dynamic organ acting locally and systemically to modulate energy homeostasis, glucose sensitivity, insulin resistance, and inflammatory pathways. Here, mass spectrometry was used to survey the proteome of patient matched subcutaneous fat and visceral fat in 20 diabetic vs 22 nondiabetic patients with morbid obesity. A similar number of proteins (~600) were identified in each tissue type. When stratified by diabetic status, 19 and 41 proteins were found to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 52 publications
2
10
0
Order By: Relevance
“…Proteomic studies of human adipose tissues provide an understanding of aberrant signaling pathways associated with DM 6 9 . Kim et al performed nano-liquid chromatography-mass spectrometry (LC–MS)/mass spectrometry (MS) analysis of human VAT and generated data suggesting cross-talk among VAT cells associated with early DM pathogenesis 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Proteomic studies of human adipose tissues provide an understanding of aberrant signaling pathways associated with DM 6 9 . Kim et al performed nano-liquid chromatography-mass spectrometry (LC–MS)/mass spectrometry (MS) analysis of human VAT and generated data suggesting cross-talk among VAT cells associated with early DM pathogenesis 7 .…”
Section: Introductionmentioning
confidence: 99%
“…There are currently no studies comparing the transcriptomes of paired human VAT, ASAT, and GFAT to better understand the differences in the molecular mechanisms between upper-and lower-body adipose tissues. Previous data-dependent proteomic analyses of whole adipose tissue detected between 17 and 600 proteins and showed that proteins involved in the extracellular matrix (29), glucose metabolism, lipid metabolism, lipid transport, response to stress, and inflammation are differentially expressed between VAT and ASAT (28,30). Proteins involved in metabolic processes such as CES, ALDH1A1, GSTP1, and FABP5 that are also associated with insulin resistance and metabolic syndrome are upregulated in VAT when compared with ASAT (28,30).…”
Section: Discussionmentioning
confidence: 99%
“…Others have profiled the whole transcriptome of human adipose tissues obtained from visceral and subcutaneous locations (25)(26)(27), which indicated that the genes involved in cellular and embryonic development, connective tissues disorders, cell morphology, lipid droplet formation and mobilization, and angiogenesis-related pathways were differentially regulated between these adipose sites. Cross-sectional analysis of the proteomes from whole VAT and ASAT (28)(29)(30) indicates that proteins associated with glucose and lipid metabolism, lipid transport, response to stress and inflammation, and nuclear receptor activation pathways were differentially regulated, whereas a recent study (31) reported few differences between the ASAT and GFAT proteomes. However, adipose tissue is composed of many cell types, including mature adipocytes, adipocyte precursors (i.e., preadipocytes), immune cells, endothelial cells, and fibroblasts (32), hence analyzing the whole adipose tissue proteome does not accurately represent the proteome of adipocytes.…”
Section: Introductionmentioning
confidence: 96%
“…Fang et al performed immune-depletion of albumin proteins after delipidation. They identified 637 protein groups in subcutaneous fat and 604 protein groups in omental fat via in-solution digests and single LC-MS runs on an LTQ-XL mass spectrometer [20]. Gomez-Serrano et al .…”
Section: Discussionmentioning
confidence: 99%
“…Proteomic analysis of adipose tissue has focused almost exclusively on human subjects and animal models of diabetes and other metabolic diseases [19]. The main tissue groups used for analysis in proteomic studies are subcutaneous and omental (visceral) fat depots, which are heavily affected in metabolic diseases [1, 20]. However, adipose tissue function affects several other medical conditions, including inflammatory diseases, parasitic infections, immune responses, and cancer [8, 2123].…”
Section: Introductionmentioning
confidence: 99%